Perceived Value and Pricing as Determinants of Loyalty Intention in Music Streaming Subscription Services: Mediating Role of Customer Satisfaction - Fibrillya Priskila Moreen Soputan; Ronny H. Walean; Deske W. Mandagi (Jurnal Economic Resource, 2026)
Customer loyalty represents a critical challenge for subscription-based digital services, particularly in the highly competitive music streaming industry. This study aims to examine the influence of perceived value and pricing on loyalty intention, with customer satisfaction serving as a mediating variable among Spotify Premium users. A quantitative research approach was employed through a survey. Data were collected from 204 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The structural model analysis reveals that perceived value and pricing have significant positive effects on customer satisfaction and loyalty intention. Furthermore, customer satisfaction significantly mediates the relationships among perceived value, pricing, and loyalty intention, indicating that satisfaction is an important mechanism linking service evaluation to loyalty behavior. The study contributes to the literature on digital consumer behavior by clarifying the mechanism through which value and price perceptions influence loyalty in subscription platforms. Practically, the findings provide insights for digital music service providers to design strategies that enhance perceived value, optimize pricing structures, and improve user satisfaction, thereby strengthening long-term customer loyalty.